3,6-Diiodo-9H-carbazole - Xie, Yu-Zhong (International Union of Crystallography, 2012)
In the title compound, C(12)H(7)I(2)N, the tricyclic aromatic ring system is essentially planar, with an r.m.s. deviation of 0.0272 Å. The two I atoms are marginally out of plane, with the C—I bonds angled at 3.9 (2) and 1.1 (2)° with respect to the planes of their respective benzene rings, above and below the plane of the carbazole ring system. No classical hydrogen bonds are observed in the crystal structure.